Pengaruh Modifikasi Belitan Stator Motor Induksi Satu Phasa Starting Kapasitor Pada Mesin Bor Meja Terhadap Arus dan Daya listrik serta Putaran Motor - Muhammad Naim (Fakultas Teknik Universitas Muhammadiyah Makassar, 2020)
A 1-phase 4-pole starting capacitor induction motor which is used as an activator of the table drilling machine has a more complicated construction because it has a centrifugal switch which is connected in series with the capacitor for its initial start and a high rotational speed of the stator field, which is 1500 rpm. While a 3-phase 6-pole induction motor has a much simpler construction because it does not require a centrifugal switch and a capacitor for its initial start with a low rotational speed of the stator field, which is 1000 rpm. This study discusses the effect of modifying the stator winding in a 1-phase 4-pole starting capacitor induction motor on the table drilling machine into a stator winding of 3-phase 6-pole induction motor on the rotation of the rotor. Modifications are carried out on the stator winding of a 1-phase induction motor by changing the number of phases, number of poles, type of winding, wire diameter and number of windings per groove. Modifications are carried out on the windings to obtain a 3-phase 6-pole 24-groove induction motor with 200 windings per groove, a wire diameter of 0.5 mm, and a winding type of spiral double layer. In our trials without a load on the induction motor the rotor rotation decreased by 33.71% from 1498 rpm to 993 rpm, and with a load decreased by 36% from 1450 rpm to 927 rpm.